2019
DOI: 10.1093/gastro/goz056
|View full text |Cite
|
Sign up to set email alerts
|

Association of polymorphisms in C1orf106, IL1RN, and IL10 with post-induction infliximab trough level in Crohn’s disease patients

Abstract: Background Trough levels of the post-induction serum infliximab (IFX) are associated with short-term and long-term responses of Crohn’s disease patients to IFX, but the inter-individual differences are large. We aimed to elucidate whether single gene polymorphisms (SNPs) within FCGR3A, ATG16L1, C1orf106, OSM, OSMR, NF-κB1, IL1RN, and IL10 partially account for these differences and employed a multivariate regression model to predict patients’ post-induction IFX levels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Moreover, a study found that IL1RN can be used as a biomarker of CD (33). IL1RN genetic variants were linked to anti-TNF medication responsiveness in CD patients (34).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study found that IL1RN can be used as a biomarker of CD (33). IL1RN genetic variants were linked to anti-TNF medication responsiveness in CD patients (34).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of C1orf106 was associated with invasive breast cancer and its poor prognosis and could be used as a novel marker to predict the aggressiveness and prognosis of breast cancer ( 38 ). In addition, 2 SNPs (rs442905 and rs59457695) in the C1orf106 gene and protein expression levels could be used to predict the therapeutic effect of infliximab in patients with Crohn’s disease ( 39 ). Based on the above, it appears particularly interesting to further explore the relationships between the C1orf106 gene and DM, C1orf106 , and CD4 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Potentially relevant parameters have been explored extensively in previous studies and several clinical risk factors were found to be associated with the therapeutic efficacy of IFX, including sex [ 6 ], duration of disease [ 7 ], albumin [ 8 ], and CRP levels [ 9 , 23 ]. However, the results are inconsistent between studies.…”
Section: Discussionmentioning
confidence: 99%